A fast, precise, in‐vivo method for micron‐level 3D models of corals using dental scanners. Issue 10 (30th August 2022) - Quigley, Kate M.
Abstract: Several sampling and measurement strategies have been developed to assess biological forms in three dimensions, including corals. However, the effectiveness (in speed and precision) of current three‐dimensional (3D) methods in scanning and model construction are challenging at small scales (μm–mm). In this paper, a practical 3D scanning and model construction tool using an intra‐oral dental scanner was assessed to measure the surface area and volume of coral juveniles across multiple species. Intra‐oral scanners using confocal imaging are fast, precise to the μm scale and safe to use with live tissue, thereby eliminating the need to harm or kill the animals. The trial was conducted at the National Sea Simulator at the Australian Institute of Marine Science. High‐quality 3D scans of individual coral juveniles were successfully generated and integrated automatically into high‐resolution (μm) mesh from point clouds. The attained average scanning efficiency was <2 min/individual, without a significant difference in speed given coral complexity or between live colonies or dead coral skeletons. Overall, this fast and precise system could become a promising tool for marine environmental surveys and restoration initiatives. This tool also removes the need to sacrifice animals for measurement analysis, thereby increasing conservation and animal welfare.